2016
DOI: 10.1080/0886022x.2016.1208516
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum renalase in hemodialysis patients: is it related to left ventricular hypertrophy?

Abstract: In our study, LVMI was correlated with dialysis vintage, residual diuresis, CRP, and hemoglobin. LVMI tends to correlate with renalase and this correlation may be significant in studies with more patient numbers. The main parameters affecting renalase levels are dialysis vintage and serum creatinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
5
5
0
Order By: Relevance
“…Consistent results were obtained by other researchers for patients undergoing both hemodialysis [2023] and peritoneal dialysis [24]. In all those studies RNLS level was determined by commercially available ELISA kit (USCN Life Science Inc., Wuhan, China) with monoclonal antibodies specific to hRenalase1 isoform.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent results were obtained by other researchers for patients undergoing both hemodialysis [2023] and peritoneal dialysis [24]. In all those studies RNLS level was determined by commercially available ELISA kit (USCN Life Science Inc., Wuhan, China) with monoclonal antibodies specific to hRenalase1 isoform.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were obtained in other studies on patients undergoing both hemodialysis [13] and peritoneal dialysis [14]. Furthermore, no association between plasma RNLS level and left ventricular hyperthrophy (LVH), a cardiac consequence of inadequate HY control, was observed [15]. Oppositely, Dziedzic et al demonstrated a positive correlation between plasma RNLS and mean arterial pressure (MAP) in HD cohort [16].…”
Section: Disscusionsupporting
confidence: 82%
“…Similar, but a bit lower levels were described by Oguz EG et al (2016); It was shown, that in hemodialysis patients serum renalase levels are significantly higher than in control group (212 ± 127 ng/ml vs. 116 ± 67 ng/ml, respectively; p<0.001) [29]. There is also a report on plasma levels of renalase in hemodialysed men, in which mean renalase levels were just 20.59 ± 32.63 ng/ml, which deviates significantly from the mentioned above results [30].…”
Section: Discussionsupporting
confidence: 66%